Preventive health examinations: protocol for a prospective cross-sectional study of German employees aged 45 to 59 years (Ü45-check) - Kalski, Linda; Greiß, Franziska; Hartung, Johannes J.; Hafermann, Lorena; Hofmann, Maja A.; Wolfarth, Bernd (Frontiers in Public Health, 2023)
Objective: Early identification of health-related risk factors is of great importance for maintaining work ability. Screening examinations can help to detect diseases at an early stage and provide more needs-based recommendations. This study aims 1) to assess the individual need for prevention or rehabilitation based on medical health examinations compared to a questionnaire survey, 2) to assess the results of the medical health examinations compared to the Risk Index – Disability Pension (RI-DP), 3) to assess the results of the questionnaire survey compared to the RI-DP, 4) to assess the general health status of the sample (target population > 1000) in German employees aged 45-59 to outline and 5) to identify which medical conditions are most common. Further study question aim 6) to investigate the general health status of the specific occupational groups. Methods: Comprehensive diagnostics including medical examination, anamnesis, anthropometric measurements, bioelectrical impedance analysis (BIA), handgrip strength, resting electrocardiogram (ECG), resting blood pressure, pulse wave velocity (PWV) and laboratory blood analyses added by a questionnaire are conducted. The research questions are analyzed in an exploratory manner. Results and Conclusion: We expect that the obtained results will allow us to formulate recommendations regarding a screening for prevention and rehabilitation needs on a more evidence-based level.